The Creation of the Cult of Josaphat Kuntsevych in the Radziwiłł Family’s Stately Magnate Home in Biała Radziwiłłowska - Wereda, Dorota (Lietuvos istorijos studijos, 2025)
At the beginning of the 18th century, the relics of Josaphat Kuntsevych were transported from Polatsk to the Radziwiłłs’ stately family home in Biała Radziwiłłowska (known since 1837 as Biała Podlaska). This was intended to be a form of temporary security for the relics during the Great Northern War and the unstable situation in the Archdiocese of Polatsk. Leon Kiszka, the Proto-Archimandrite of the Basilian Order, decided that the protector of the relics should be the Grand Chancellor of Lithuania, Karol Stanisław Radziwiłł, after unsuccessful efforts were made with Lithuania’s Field Hetman Michał Serwacy Wiśniowiecki. The Radziwiłłs placed the relics in the family’s chapel at the castle, where one of the altars was dedicated to Josaphat; however, they did not take any initiative to spread the cult of the relics. They also returned to Leon Kiszka the magnificent reliquary, in the form of a silver coffin, in which the relics had been displayed in Polatsk. This situation did not change until after 1743 following a decision made by the Basilians at a monastic chapter meeting in Dubno, during which, a compromise was worked out between the Basilian Order and the Radziwiłłs concerning the further fate of the relics. The relics remained in Biała Radziwiłłowska on condition that the Radziwiłłs would finance the building of a new church to house them. In 1743, Anna Radziwiłł issued a foundation document in which she guaranteed funds for the maintenance of six singers who were obliged to sing during liturgies and participate in religious ceremonies in the castle chapel. The Radziwiłłs began to hold indulgence ceremonies at the castle for invited guests from the elite. The setting for these religious ceremonies mimicked the lavish and spectacular Baroque ceremonies of magnate courts. Josaphat was regarded as the noble family’s intercessor in matters of health. The cessation of public worship of the relics for more than half a century contributed to the involvement of the Uniate Church’s elite in the creation of Marian cult sites and efforts to organize coronation ceremonies at which papal crowns would be placed on cult images of the Virgin Mary (Zhyrovichy, Chełm). The consequence of the absence of the martyr’s cult centre was the loss of the status of a supra-local cult and the abandonment of forms of worship adequate to the position of the patron of the Polish Crown and the Grand Duchy of Lithuania (proclaimed at the 1673 Sejm).